Effects of inspections on plants' regulatory and environmental performance - evidence from Norwegian manufacturing industries - Kjetil Telle (Statistics Norway, Research Department, 2004)
The present paper investigates effects of regulatory inspections on compliance and emissions of energy intensive manufacturing plants in Norway. The regression analysis shows that increased probability of inspection reduces the probability of violation. This is in line with previous studies, and may appear as an encouraging evaluation of the practiced regulatory enforcement policy. However, the direct environmental impact of the enforcement policy is more dubious: Regression analyses reveal a positive relationship between the probability of an inspection and emissions. It appears puzzeling that increased probability of inspection can yield both reduced probability of violation and higher emissions. The possibility that such a puzzle evolves from incentives inherent in the practiced regulatory policy is discussed.
Keywords: K42; Q28; L51; K32; 330; Environmental regulations; regulatory enforcement; inspections; emissions